NEGOTIATING CULTURAL IDENTITY OF MEI LEE IN TURNING RED (2022) - Tsabita Putri Ibrahim; Ayu Saraswati (ELite Journal : International Journal of Education, Language and Literature, 2026)
In the era of globalization, second-generation immigrants often face complex challenges in negotiating their cultural identity as they balance heritage values with the norms of their host country. This study aims to analyze how the main character in the film Turning Red (2022) negotiates her cultural identity within a Chinese-Canadian family. This study applies Will Kymlicka’s (1995) theory of multiculturalism as an analytical approach, focusing on the concepts of polyethnic rights and internal restrictions. This research uses a qualitative content analysis with the main data source in the form of dialogue. The findings indicate that the main character, Mei, initially experiences strong internal restrictions imposed by her family, which limit her individual autonomy. However, as the film progresses, she gradually asserts her individuality and redefines her identity. She can finally control the inner red panda within herself that will come out whenever she is too emotional, and it symbolizes the success in balancing her sense of belonging to her culture with her individual autonomy.